Factors affecting the quality of external audit and its relation to financial corruption in the Algerian economic institution from an academic and professional standpoint - benharkou, ghania; bouhafs, samiha; maatouk, Samia (Journal of Research in Finance and Accounting, 2026)
This study aims to clarify the factors affecting the quality of external audit and its relationship to financial corruption in the Algerian economic institution. In order to obtain the necessary and more relevant data, a questionnaire was used for a sample of professionals and academics. The study concluded that the concept of financial corruption in economic institutions varies from job to job. Academics' responses are based on a scientific expectation, whereas professional accountants' responses are based on reality and their perspective on financial corruption in Algerian economic institutions.